Easy synthesis of organic–inorganic hybrid nanomaterials: study of DC conduction mechanism for light dependent resistors. Issue 37 (29th March 2016) - Rawal, Ishpal; Tripathi, Ravi Kant; Panwar, O. S.
Abstract : Polypyrrole/SnO2 hybrid nanostructures have been analyzed for futuristic non-toxic light dependent resistors. Abstract : A surfactant assisted chemical oxidation method has been employed for facial synthesis of polypyrrole/tin oxide (PPy/SnO2 ) hybrid nanoneedles. The charge transport properties of the prepared hybrid nanomaterials have been analyzed under different conduction mechanisms for their possible application for light dependent resistors (LDRs). The scanning electron microscopy studies revealed that the increased concentration of additive SnO2 quantum dots alters the surface morphology from nanowall-like to nanoneedle-like and the formation of PPy/SnO2 nanocomposites is confirmed X-ray diffraction studies. The strong coupling between the PPy and SnO2 results in the transformation of PPy from highly oxidized states to oxidized states and is confirmed through Raman analysis. The simple band conduction model and Kivelson's power law based conduction mechanism could not be applied to explain the conduction mechanism due to different reasons. The log σ dc curves for all samples were well fitted for γ = 1/4, suggesting the applicability of Mott's three dimensional variable range hopping VRH model for charge transport. The room temperature dark conductivity of the samples was found to decrease with an increase in SnO2 concentration. The formation of p–n junctions between p-type PPy and n-type SnO2 changes the bandgap of PPy and the work function. This modifies the electronic structure of PPy which brings a synergistic effect in the photosensitivity of the PPy/SnO2 nanocomposites. The room temperature photoresponse of the PPy/SnO2 samples was found to increase from 2.85 to 6.25% at 100 mW cm −2 illumination intensity with an increase in the SnO2 doping concentration from 0 to 20%.